2012
DOI: 10.1111/j.1540-5885.2012.00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Directive Deficiencies: How Resource Constraints Direct Opportunity Identification in SMEs

Abstract: Previous studies show that resource constraints have mixed effects on innovation and opportunity identification by entrepreneurs. Sometimes, resource constraints lead to identifying more opportunities, whereas in other cases, entrepreneurs see fewer opportunities. This study explores a new approach to reconcile this inconsistency. Using a sample of 219 small‐ and medium‐sized enterprises (SMEs), we explore relationships between supply and demand constraints, on the one hand, and identifying supply and demand o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 78 publications
(156 reference statements)
2
36
0
5
Order By: Relevance
“…The dependent variable measured the number of sustainable opportunities identified in eight categories which were collapsed into two categories (low opportunity identification and high opportunity identification), which gives a dichotomous dependent variable. Linear regression becomes inappropriate for categorical dependent variables because it relies on the assumption of normality of residuals [89,90]. Consequently, hierarchical logistic regression analysis was used to test the hypotheses H1-H4c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependent variable measured the number of sustainable opportunities identified in eight categories which were collapsed into two categories (low opportunity identification and high opportunity identification), which gives a dichotomous dependent variable. Linear regression becomes inappropriate for categorical dependent variables because it relies on the assumption of normality of residuals [89,90]. Consequently, hierarchical logistic regression analysis was used to test the hypotheses H1-H4c.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could focus on the type of sustainable opportunities identified (see [89]). Furthermore, we could not separate the number of sustainable opportunities identified for making an existing business more sustainable from the number of opportunities identified for starting a new sustainable business.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, those studies that did include this variable in their models reported inconsistent results, including positive (e.g., Faraj and Yan, 2009), negative (e.g., Sethi and Iqbal, 2008), and nonsignificant (e.g., Hoegl and Parboteeah, 2006) relationships. This is in contrast to studies on the organizational level, where material resource adequacy as a focal variable was studied extensively (Garriga, Von Krogh, and Spaeth, 2013;Katila and Shane, 2005;Nohria and Gulati, 1996;Troilo, De Luca, and Atuahene-Gima, 2014;van Burg, Podoynitsyna, Beck, and Lommelen, 2012). Even more problematically, the role of material resource adequacy in innovation project performance from an academic perspective is as unclear as it is in practice, with contradictory theoretical assumptions as well as empirical findings (Hoegl, Gibbert, and Mazursky, 2008;Rosso, 2014).…”
Section: Introductionmentioning
confidence: 87%
“…The most striking and compelling take-away is that the strong and sustained innovative and economic performance exhibited by the Mittelstand stems not from access to a sole resource but rather from participating in a highly effective context that bestows innovation and competitiveness in global markets. Any one aspect alone (whether it be a niche focus, globalization strategy, preference for self-financing, long-run mindset, superior employee relations, or community embeddedness), Resource-based view (Alvarez and Barney, 2007;Barney, 1991Barney, , 2001Foss, Klein, Kor, and Mahoney, 2008 Entrepreneurship and innovation literature (Baker and Nelson, 2005;Corbett, Covin, O'Connor, and Tucci, 2013;Sarasvathy, 2001;Stock, Zacharias, and Schnellbaecher, 2016;Van Burg et al, 2012;Williams and Wood, 2015;Zahra and Wright, 2011) and interorganizational drivers of heterogeneity in the six capabilities for innovating with limited resources? RQ #2C: Do Mittelstand firms have superior capabilities as compared to other firms?…”
Section: Research Implications and Conclusionmentioning
confidence: 99%